Microstructure and corrosion properties of 625 Ni-based alloy surfacing layer on the inner-wall of oil pipe prepared by twin tungsten electrode TIG welding with heat wire - Juan PU; Sutong SHI; Hongbing WEI; Mingfang WU; Huawei SUN; Weimin LONG (Hanjie xuebao)
Two Inconel 625 Ni-based alloy surfacing layers were prepared on the inner wall of high-strength steel in oil pipeline by using double tungsten electrode TIG technology with hot wire that was controlled by independent power supply. The samples obtained from the oil pipeline were solution treated at the temperature of 800 ℃ and 900 ℃, respectively. The microstructure and composition of Ni/steel surfacing plates were analyzed by optical microscope (OM) and scanning electron microscope (SEM). Its hardness and electrochemical corrosion resistance were tested and its passive film was analyzed by X-ray photoelectron spectroscopy (XPS). The results showed that in the as-welded state, the first layer of Ni-based surfacing alloy grew upwards in order perpendicular to the steel, however, the second layer nucleated on the substrate and from precipitates in the substrate of the first layer alloy, and its growth sequence became chaotic. Meanwhile, the grain size of the first layer was smaller than that of the second layer owing to the heat effect of the second layer on the first layer. After solid solution treatment, the microstructure of HAZ became more uniform and refined compared to that in the as-welded state, and this could improve the strength and toughness of the Ni/steel interface. In the as-welded state, the microstructure of Ni/steel surfacing composite plate presents a gradient distribution, which shows that the Ni/steel surfacing layer (220 HV) is significantly higher than that of the high strength steel substrate (140 HV), and the steel matrix HAZ has the lowest hardness (100 HV) due to the microstructure softening caused by the welding heat cycle. The process of solid solution treatment can increase the corresponding hardness, especially, when the solid solution treatment temperature was 800 ℃, secondary Ni-based austenite γ" phase, whose dislocation density was large, started to form, thus the hardness value of Ni-based alloy was up to the maximum. Moreover, when the solution treatment temperature was 800 ℃, the dissolution of Nb and Mo elements increased, the Laves phase and carbide phase reduced, and the needle-like δ phase appeared, thus the corrosion resistance of Ni-based alloy reached the optimal value. The passivation film was composed of two layers that the inner layer consisted of Cr, Fe, Nb, Mo oxides and the outer layer consisted of Cr, Fe, Nb, Mo hydroxide.